Entrepreneurship and Asymmetric Information in Input Markets - Robin Boadway; Motohiro Sato (Queen's University, Department of Economics, 2006)
Entrepreneurs starting new firms face two sorts of asymmetric information problems. Information about the quality of new investments may be private, leading to adverse selection in credit markets. And, entrepreneurs may not observe the quality of workers applying for jobs, resulting in adverse selection in labor markets. We construct a simple model to illustrate some consequences of new firms facing both sorts of asymmetric information. Multiple equilibria can occur. Stable equilibria can be in the interior, or at a corner in which no entrepreneurs enter. Stable interior equilibria can involve involuntary unemployment, as well as credit rationing. Equilibrium outcomes mismatch workers to firms, and will generally result in an inefficient number of new firms. With involuntary unemployment, there will be too few new firms, but with full employment, there may be too many or too few. Taxes or subsidies on new firms and employment can be used to achieve a second-best optimum. Alternative information assumptions are explored.
Keywords: D82; G14; H25; 330; entrepreneurship; asymmetric information; adverse selection